Perspectives of Small Scale Tea Growing System (Stgs) : A Study of North Bengalareas In India - Avrajyoti Ghosh, Litan Das, P. K. Pal, A. Sarkar and M. S. Nain, (Indian Journal of Extension Education, 2017)
Tea cultivation in small individual holdings in a commercial mode is a recent phenomenon and started in UpperAssam during late seventies and early eighties. In West Bengal, history of small tea growing witnessed majorchange due to sudden drop of pineapple prices in northern part of the state converting erstwhile pineapple fieldsinto tea during nineties. Having estate orientation, historically, tea is associated with prestige and dignities in thesociety. People from peasantry background feel an awe to be associated with it and it fulfills the gratification of ruralyouth to be regarded as the uplifted class. Gradually, based on comparative economic advantage, the traditionalcrop areas had been diverted to small tea growing sector. The present study was undertaken in Jalpaiguri and UttarDinajpur districts having around 80% of total small tea growers of the state during 2014-15. Study revealed that themaximum number of farmers resorted tea cultivation between 2005 to 2009 and neighbours were the main motivatingactors in conversion. Pre-planned expenditure support to the family, best substitute for existing niggling farmenterprise, neighbour’s success, higher relative net profit and existence of good marketing channels for tea weresome of the strongest reasons for resorting tea cultivation in North Bengal. Highest family education status,outside contact behaviour and media communication had significant positive correlation with the earliness ofconversion to tea. So, small tea growing system can grab the rural educated youth into it and may be a promisingenterprise for attracting rural youth in farm entrepreneurship